Consumerism in Samrat Upadhyay's Buddha's Orphans - Pokharel, Suman (NPRC Journal of Multidisciplinary Research, 2025)
Background: In the novel Buddha's Orphans (2010), the Nepali-American novelist Samrat Upadhyay (b. 1964) captures the notion of consumerism prevalent in Kathmandu city from the 1950s to the early 2000s. The author's presentation regarding the protagonists' longing and desire for material goods provides a wide area to explore in relation to the theme of consumerism.Method: This study employs Jean Baudrillard's concept of consumerism to observe the consuming habits of the characters throughout the novel. This study applies the close reading and the textual analysis approach as a methodology to explore consumerism within the text.Result: The study reveals that most of the novel's characters are driven by the societal concern about consumerism. The novel's characters struggle to maintain societal status through their belongings.Conclusion: The protagonists Raja and Nilu in the novel are aware of society's consumer habits. They continuously try to create identity through the things they have won. The desire to elevate their social status motivates them to work hard, and by the end of the novel, they successfully achieve it.Novelty: The aim of getting more, consuming more, and showing more is the perfect way to observe the theme of consumerism in the text. The characters are anxious about their social reputation, so they compete to maintain their living standards through their consumption habits, which helps us to delve into the depth of consumerism in the novel.